Pendampingan Guru dan Komite SMK dalam Penguatan Pembelajaran Mendalam dan Karakter Siswa Berbasis Kurikulum Merdeka: Pengabdian - Lisa Virdinarti Putra; Nur Intan Rochmawati; Wiwik Pudjaningsih; Aulia Cahyaning Tyas; Bagas Prakosa (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service program aims to improve teachers' pedagogical competence and strengthen collaboration between teachers and school committees in implementing the Independent Curriculum in vocational high schools through a deep learning approach. The activity focused on two partner schools, SMK Putra Bangsa Salatiga and SMK Bina Nusantara Ungaran, which were selected because initial assessments indicated that teachers' understanding of Project-Based Learning (PjBL) design and practice, as well as the integration of deep learning values, was still limited. The program lasted four months (September–December 2025) using the Participatory Action Research (PAR) method, which actively involved participants from needs identification, training, mentoring, to reflective evaluation. The activity involved 48 teachers and 10 school committee members. The results showed a 34.2% increase in teachers' ability to design and implement PjBL and a 29.5% increase in teacher-committee collaboration based on a paired t-test (p < 0.05). Observations and interviews also demonstrated increased teacher motivation and creativity in implementing the deep learning approach, particularly in strengthening students' character, independence, and critical thinking.